Interferon gamma: a crucial role in the function of induced regulatory T cells in vivo. - Wood, K; Sawitzki, B (2006)
Interferon (IFN)gamma can have paradoxical functions, eliciting inflammatory T helper 1 (Th1)-driven immune responses in some circumstances, and enabling induced regulatory T (Treg) cells to control immune responses in others. Here, we propose a model in which IFNgamma produced rapidly and only transiently by induced Treg cells is crucial to their function in vivo. This early production of IFNgamma by induced Treg cells during an immune response can directly inhibit the activation and proliferation of IFNgammaR1- and IFNgammaR2-bearing T cells. Furthermore, it can indirectly prevent further T-cell activation by creating a microenvironment that influences the function of antigen-presenting cells (APCs) as a result of IFNgamma-induced inducible nitric oxide synthase (iNOS), indoleamine-2,3-dioxygenase (IDO) and heme oxygenase (HO)-1 expression.